A study on poor prognostic factors associated with ventilator associated pneumonia at a tertiary care hospital - R., Raveendra K.; Hegde, Suraj S. (International Journal of Advances in Medicine, 2020)
Background: Ventilator associated pneumonia (VAP) is a hospital acquired infection (HAI) seen among critically ill patients, on mechanical ventilation, due to various causes in intensive care units (ICUs). It is associated with increased morbidity and mortality which increases the cost of health care. The aim of this study was to determine the poor prognostic factors associated with VAP. Methods: In this cross-sectional prospective study,40 patients who developed features of ventilator associated pneumonia on a platform of mechanical ventilator for >48 hrs in ICU were included in the study. VAP was then diagnosed based on clinical pulmonary infection scoring system (CPIS) with a score of >=6. All patients were evaluated and correlated with different parameters for the treatment and outcome. Results: Most of the patients had late onset VAP (60.7%) with average number of days being around 8 days. Pseudomonas, Acinetobacter, Enterobacteriacea, Staphylococcus aureus were commonly isolated organisms. Polymicrobial infections were not detected. Antibiotics like colistin, tigecycline and beta-lactamases are the most commonly effective antibiotics. Of the 40 VAP patients,20 patients survived and 20 died with protocol line of treatment. Following poor prognostic factors were identified-Early onset VAP (42.5%), elderly patients (>65 years) (90%), Type 2 DM (80%), hypertension (70%), prior antibiotic therapy (65%), prolonged supine position (68%) and re-intubation (75%). Conclusions: Ventilator associated pneumonia is associated with a significant increase in length of stay in ICU, time of mechanical ventilation and different complications and certain risk factors further worsens the prognosis.